2022
DOI: 10.35772/ghm.2022.01003
|View full text |Cite
|
Sign up to set email alerts
|

Changes in parental involvement and perceptions in parents of young children during the COVID-19 pandemic: A cross-sectional observational study in Japan

Abstract: This study aimed to clarify changes in parental involvement with their children and parental perceptions related to parenting in both fathers and mothers of young children during the coronavirus disease 2019 (COVID-19) pandemic. A cross-sectional observational design was used. Data were collected using a web-based questionnaire from 28 fathers and 115 mothers between October 1 and November 30, 2020. Parents answered questions regarding themselves, basic sociodemographic variables, perceived changes in involvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Adjusted residuals are calculated by dividing the raw residual by the square root of the expected value as an estimate of the raw residual's standard deviation, which is also provided by SPSS (Sharpe, 2015). Usually, an adjusted residual exceeding ±1.96 indicates that the number of cases in that cell is significantly larger or smaller than expected, with a significance level of 0.05 (IBM, 2020;Nomura et al, 2022). Finally, multiple linear regressions were performed to examine whether emotional expression and management using emojis were associated with depressive symptoms and subjective happiness (H4).…”
Section: Data Analysis and Emoji Codingmentioning
confidence: 99%
“…Adjusted residuals are calculated by dividing the raw residual by the square root of the expected value as an estimate of the raw residual's standard deviation, which is also provided by SPSS (Sharpe, 2015). Usually, an adjusted residual exceeding ±1.96 indicates that the number of cases in that cell is significantly larger or smaller than expected, with a significance level of 0.05 (IBM, 2020;Nomura et al, 2022). Finally, multiple linear regressions were performed to examine whether emotional expression and management using emojis were associated with depressive symptoms and subjective happiness (H4).…”
Section: Data Analysis and Emoji Codingmentioning
confidence: 99%
“…Many studies of parents having children during the COVID-19 pandemic have suggested several unique characteristics. For example, some studies reported that parents experienced positive changes, such as increased association and familiarity between parents and children, because they spent more time at home (5)(6)(7). On the other hand, other studies reported that parents showed dangerous characteristics such as increased mental distress regarding parenting or increased violence towards their children (8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that parents experienced an increasing burden of parenting or parental distress during this pandemic. 1,2 Adverse effects on parents tend to negatively reflect in their parenting and cause inadequate parental behavior. Some international institutions have warned about the rise of child abuse during the pandemic.…”
Section: Introductionmentioning
confidence: 99%